2008
DOI: 10.1016/j.mce.2008.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor beta (TGFβ1, TGFβ2 and TGFβ3) null-mutant phenotypes in embryonic gonadal development

Abstract: The role transforming growth factor beta (TGFb) isoforms TGFb1, TGFb2 and TGFb3 have in the regulation of embryonic gonadal development was investigated with the use of null-mutant (i.e. knockout) mice for each of the TGFb isoforms. Late embryonic gonadal development was investigated because homozygote TGFb null-mutant mice generally die around birth, with some embryonic loss as well. In the testis, the TGFb1 null-mutant mice had a decrease in the number of germ cells at birth, postnatal day 0 (P0). In the tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 50 publications
(58 reference statements)
4
52
0
Order By: Relevance
“…Gene knockout studies have demonstrated that FGF9 signalling is essential for testis development, but deletion of activin or TGFβ genes have relatively mild effects (Shull et al 1992, Colvin et al 2001, Schmahl et al 2004, Kim et al 2006, 2007, Bagheri-Fam et al 2008, Memon et al 2008, Archambeault & Yao 2010, Moreno et al 2010, Mendis et al 2011. Consistent with this, this study demonstrated that ex vivo exposure of XX gonads to FGF9 promoted changes in XX gonad characteristic of the developing testis, including supporting cell proliferation, repression of ovarian genes and promotion of male germ line development.…”
Section: Growth Factors Fgf9 Activin and Tgfβ Promote Testicular Chasupporting
confidence: 68%
See 1 more Smart Citation
“…Gene knockout studies have demonstrated that FGF9 signalling is essential for testis development, but deletion of activin or TGFβ genes have relatively mild effects (Shull et al 1992, Colvin et al 2001, Schmahl et al 2004, Kim et al 2006, 2007, Bagheri-Fam et al 2008, Memon et al 2008, Archambeault & Yao 2010, Moreno et al 2010, Mendis et al 2011. Consistent with this, this study demonstrated that ex vivo exposure of XX gonads to FGF9 promoted changes in XX gonad characteristic of the developing testis, including supporting cell proliferation, repression of ovarian genes and promotion of male germ line development.…”
Section: Growth Factors Fgf9 Activin and Tgfβ Promote Testicular Chasupporting
confidence: 68%
“…Blocking activin/TGFβ signalling at E11.5 or E12.5 significantly reduces Sertoli cell proliferation and disrupts testis cord formation , indicating that activin-TGFβ signalling promotes testis formation in the critical sex-determining window at E11.5. However, testes develop in mice that lack Inhba, Inhbb or individual Tgfβ genes, demonstrating that they are individually dispensable for male sex determination (Shull et al 1992, Memon et al 2008, Archambeault & Yao 2010, Moreno et al 2010, Mendis et al 2011, although the possibility that these factors compensate for one another's function in testis development has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…As the central component of canonical TGF-β superfamily signaling, deletion of SMAD4 should eliminate canonical TGF-β signaling to the Sertoli cells (24). Although numerous TGF-β superfamily ligands, including AMH, TGF-β1, TGF-β2, TGF-β3, and activin B are produced in embryonic testes, testis cord dysgenesis has not been reported in murine models lacking these genes (19,(25)(26)(27). We therefore hypothesized that any changes in testis cord development in the Sertoli-specific Smad4 conditional knockout model (Amh cre/+ ;Smad4 fl/− or Smad4 cKO) would result from the inability of Sertoli cells to respond to fetal Leydig cell-derived activin A.…”
Section: Sertoli Cell-specific Ablation Of Smad4 Recapitulates Testismentioning
confidence: 99%
“…Furthermore, a TGF-bRII knockout experiment likewise verified that TGF-b plays an important role in germ cell proliferation and apoptosis. Stéphanie et al (2010), Memon et al (2008), and others have also shown that TGF-b1 and TGF-b3 are both expressed in mouse embryonic testes, and Mai et al (2010) noted that TGF-b is necessary for testis development following a functional defect analysis in mice.…”
Section: Bmp4 Promotes Escs To Differentiate Into Male Germ Cellsmentioning
confidence: 99%